Utilisation Of Coal Mining Wastewater As Sanitation Water At Pt Putra Perkasa Abadi Site Borneo Indobara - Rozzaq Al hanif Islamudin*; Trio Aris Chrisdianto; Dini Sabila; Mursal Mursal (Universitas Syiah Kuala, 2023)
The need for sanitation and operational water supply requires a good source of water with long-lasting and sustainable availability. Therefore, it is necessary to have a water source solution in large quantities and continuously. In this case, PT Putra Perkasa Abadi, a coal mining service contractor company, converts water sources from coal mining waste in the IUP (Mining Business License) area of PT Borneo Indobara into water for sanitation activities. The purpose of this research is to utilise coal mining waste waste water into sanitation water. This research method uses quantitative and qualitative research methods. The results showed that the implementation of the utilisation of coal mining wastewater as sanitation water at PT Putra Perkasa Abadi was able to eliminate the use of groundwater to 100% surface water. The process starts from stagnant Acid Mine Drainage in the sump being pumped to the sediment pond then treated using the precipitation method and then flowed through the pipe to the Water Treatment Plant (WTP) to be processed into sanitary water. This WTP uses the precipitation method and provides coagulants with the aim that water quality complies with Indonesian government regulations referring to Permenkes RI No. 02 of 2023. From the results of the initial analysis, the quality standard value is obtained with a value of Ph: 5.96, TDS: 520 mg/L and Turbidity 1.2 NTU. with the results after WTP treatment being pH: 7.93, TDS: 43,525 mg/L and Turbidity 0.84 NTU. Re-utilisation of mine waste discharge water is very effective for supplying domestic water needs in the operational area of PT Putra Perkasa Abadi. The monthly water usage reaches 10,000-12,000 M^3. The data is an interpretation of the description of water usage for sanitation operational support activities. The abundant source of acid mine drainage supported by high rainfall makes it possible not to use groundwater at all in the coal mining area.